Differentiation from first principles f(x+h) A f(x) x x + h Gradient of AP =
Differentiation from first principles f(x+h) A f(x) x x + h Gradient of AP =
Differentiation from first principles f(x+h) A f(x) x x + h Gradient of AP =
Differentiation from first principles f(x+h) A f(x) x x + h Gradient of AP =
Differentiation from first principles f(x+h) A f(x) x x + h Gradient of AP =
Differentiation from first principles f(x) x Gradient of tangent at A =
Differentiation from first principles f(x) = x2
Differentiation from first principles f(x) = x3